High-sensitivity image encryption algorithm with random diffusion based on dynamic-coupled map lattices. (November 2019) - Wang, Xingyuan; Zhao, Hongyu; Feng, Le; Ye, Xiaolin; Zhang, Hao
Highlights: Logistic-dynamic mixed linear-nonlinear coupled map lattices (LDMLNCML) was proposed. A new image encryption algorithm was proposed. The method of random diffusion was proposed. Our algorithm is the first to study random diffusion. The strategy of simultaneously shuffling and diffusion was adopted. Only need one round of encryption to ensure the security of the algorithm. which can make up for the shortcomings of traditional methods with regard to efficiency or security. Abstract: This paper proposes a new high-sensitivity image encryption algorithm with random diffusion based on the spatiotemporal chaos of the Logistic-dynamic mixed linear-nonlinear coupled map lattices (LDMLNCML). The proposed LDMLNCML system possesses prominent cryptographic characteristics, which is very suitable for image encryption. The proposed image encryption algorithm adopts the strategy of random diffusion. Firstly, the pending sequence is generated according to the number of image pixels, and then two index chains are generated combining the conflict handling process. Finally, the cipher image is obtained by random diffusion. Index chains are highly sensitive to changes in position, and changes of the position of any one element will produce completely different index chains. The cipher value of each pixel in the diffusion phase depends on two random non-adjacent pixels and chaos interference value, which can greatly reduce the correlation between the adjacent pixels. Theoretical analysis and experimental results demonstrate the security and practicability of the cryptosystem.